Evaluation of wound healing and anti-inflammatory activities of a herbal ointment consisting of Althaea officinalis, Lavandula angustifolia, and Rosa x damascena in animal excision wound model - Saeideh Momtaz; Amirhossein Abdolghaffari; Eghbal Jasemi; Bahman Yaghoobvand; Saeed Esmaeilzadeh; Alireza Abdollahi; Mohammad Abdollahi (Institue of Medicinal Plants, ACECR, 2021)
Background: Althaea officinalis L., Lavandula angustifolia Mill. and Rosa x damascena Herrm. are used to treat excision or burn lesions in traditional medicine. Objective: To evaluate the healing effect of a polyherbal ointment containing L. angustifolia, R. x damascena, and A. officinalis combination on wounds caused by third grade skin cut. Methods: To evaluate the wound healing effect of this polyherbal formulation, an ointment containing the extract of A. officinalis, the essential oil of R. x damascena (2 % essence) and the essential oil of L. officinalis (2 % essence) in an eucerin base (20:20:10:50) was prepared. The formulation was examined using excision wound test for 14 days and the percentage of healing effect in each group was calculated. Formalin induced rat hind paw edema method was used for determination of anti-inflammatory activities of the same formulation. Results: The percentage of recovery in the polyherbal formulation group was significantly higher than the other groups. Histological studies also confirmed these results. Herbal formulation treated group showed significant improvement in terms of re-epithelialization, angiogenesis, collagen deposition, and reducing inflammation. The percentage of wound healing was 99.07 ± 0.34, 99.22 ± 0.35, 98.45 ± 0.733, 98.75 ± 0.88 and 63.72 ± 5.64, for the polyherbal formulation, L. angustifolia, R. damascena, A. officinalis extracts, and the placebo group, respectively. Conclusion: This polyherbal formulation could act as a wound healing agent, possibly due to the suppression of inflammatory mediators. The presence of phenolic compounds might be a reason behind the therapeutic effect of these plants.